2022
DOI: 10.1177/09721509211060616
|View full text |Cite
|
Sign up to set email alerts
|

How Does COVID-19 Affect the Volatility Spillover Between the Exchange Rate and the Export-oriented Businesses in Iran?

Abstract: This study concentrates on examining the volatility spillover effects between the exchange rate (IRR to USD) and the leading export-oriented industries (i.e., petrochemical, basic metals and minerals) in Tehran Stock Exchange before and after the COVID-19 pandemic. Using DCC- and asymmetric DCC-GARCH approaches, the data sample (from 15 December 2018 to 24 April 2021) has been partitioned into two sub-samples: before and after the official announcement of COVID-19 outbreak. The results demonstrate that from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…When these studies are examined, it has been observed that some of the studies focused on the effects of the pandemic on stock market volatility (Baek, Mohanty and Glambosky, 2020;Mirza, Naqvi, Rahat and Rizvi, 2020;Albulescu, 2021;Izzeldin, Muradoğlu, Pappas and Sivaprasad, 2021;Shahzad, Naeem, Peng and Bouri, 2021;Christopoulos, Kalantonis, Katsampoxakis and Vergos, 2021;Engelhardt, Krause, Neukirchen and Porsch, 2021;Topcu, Yagli and Emirmahmutoglu, 2021;Uddin, Chowdhury, Anderson and Chaudhuri, 2021;Wang, Xu and Sharma, 2021;Bakry et al, 2022;Diaz, Henríquez, and Winkelried, 2022;Sreenu and Pradhan, 2022;Vera-Valdes, 2022;Xu, 2022). In addition, exchange rate returns volatility (Feng, Yang, Gong and Chang, 2021;Honarmandi and Zarei, 2022;Yıldırım, Erdoğan and Tarı, 2022;Geng and Guo, 2022), stock return (Yiu and Tsang, 2022;Handoyo, Ibrahim and Indrawan, 2022); returns and volatility (Rakshit and Neog, 2021;Bissoondoyal-Bheenick, Do, Hu and Zhong, 2021;Pyo, 2021;Ozdemir, Ercan, Grima and Romānova, 2021;Song, Bouri, Ghosh and Kanjilal, 2021;Li et al ., 2021;Kusumahadi and Permana, 2021;Wasiuzzaman, 2022), exchange rate returns and return (Torbecke, 2021;Narayan, 2022b), stock price and exchange rate returns (Hoshikawa and Yoshimi, 2021;Rai and Garg, 2022;), liquidity and return (Park and Newaz, 2021;…”
Section: Literature Reviewmentioning
confidence: 99%
“…When these studies are examined, it has been observed that some of the studies focused on the effects of the pandemic on stock market volatility (Baek, Mohanty and Glambosky, 2020;Mirza, Naqvi, Rahat and Rizvi, 2020;Albulescu, 2021;Izzeldin, Muradoğlu, Pappas and Sivaprasad, 2021;Shahzad, Naeem, Peng and Bouri, 2021;Christopoulos, Kalantonis, Katsampoxakis and Vergos, 2021;Engelhardt, Krause, Neukirchen and Porsch, 2021;Topcu, Yagli and Emirmahmutoglu, 2021;Uddin, Chowdhury, Anderson and Chaudhuri, 2021;Wang, Xu and Sharma, 2021;Bakry et al, 2022;Diaz, Henríquez, and Winkelried, 2022;Sreenu and Pradhan, 2022;Vera-Valdes, 2022;Xu, 2022). In addition, exchange rate returns volatility (Feng, Yang, Gong and Chang, 2021;Honarmandi and Zarei, 2022;Yıldırım, Erdoğan and Tarı, 2022;Geng and Guo, 2022), stock return (Yiu and Tsang, 2022;Handoyo, Ibrahim and Indrawan, 2022); returns and volatility (Rakshit and Neog, 2021;Bissoondoyal-Bheenick, Do, Hu and Zhong, 2021;Pyo, 2021;Ozdemir, Ercan, Grima and Romānova, 2021;Song, Bouri, Ghosh and Kanjilal, 2021;Li et al ., 2021;Kusumahadi and Permana, 2021;Wasiuzzaman, 2022), exchange rate returns and return (Torbecke, 2021;Narayan, 2022b), stock price and exchange rate returns (Hoshikawa and Yoshimi, 2021;Rai and Garg, 2022;), liquidity and return (Park and Newaz, 2021;…”
Section: Literature Reviewmentioning
confidence: 99%